Pola Pengembangan Islam Datuk Mad Yudha (Datuk Sri Diraja) Dalam Mengembangkan Islam di Kerajaan Lima Laras Kab. Batu bara - Fauziah Luthfiah (UIN Sumatera Utara, 2021)
This article aims to explore the history and development of Islam in the Lima Laras Kingdom which was carried out by Datuk Mad Yudha. The results of this study have found several things about Datuk Mad Yudha in terms of the development of Islam in his time. Datuk is a leader for the Malay community in the Lima Laras Kingdom. He had great attention to the development of Islam in his time. The development of Islam in Lima Laras used to be very fast, because in the past Datuk Mad Yudha had a Mufti named H. Arfah, he was often an advisor in the field of religion. And as a leader he was formerly a king who adhered to the Naqsabandiyah Terekat, he succeeded in building Islamic civilization at that time. And in developing Islam Datuk Mad Yudha also uses several media, namely the first Ulama whose job is to solve problems that exist in the kingdom and among the community in terms of religion. both mosques as a very important medium for worship. The three cannons as tools and media to gather the public. The four Tarekat are media that function to develop Islam in the Five Laras Kingdom. The fifth trades and the last is OK as media in the area to help him in leading.